Empowering communities in mangrove ecotourism: A pathway to sustainability and climate resilience in Bengkulu City - Srifitriani Abditama; Soeprobowati Tri Retnaningsih; Puryono Sri (E3S Web of Conferences)
This study examines how empowering local communities contributes to the planning, utilization, and management of Bhadrika Mangrove Ecotourism Park in Bengkulu City, advancing sustainability and climate resilience. Using a descriptive quantitative approach, 27 household heads from RT 08 Lingkar Barat were surveyed to assess their participation. The results indicate substantial community involvement in planning (73.03%), utilization (72.27%), and management (74.48%), all categorized as “good.” This active engagement promotes sustainable ecotourism, environmental preservation, and socio-economic development. However, issues such as limited infrastructure and low public awareness persist. Enhancing community roles through education, innovative approaches, and sustainable resource utilization is crucial to fully realize the ecological and social potential of mangrove ecotourism. The findings underscore the importance of community-driven initiatives in achieving ecosystem sustainability and climate change resilience.